2022
DOI: 10.1007/s12035-022-02976-3
|View full text |Cite
|
Sign up to set email alerts
|

Linking Inflammation, Aberrant Glutamate-Dopamine Interaction, and Post-synaptic Changes: Translational Relevance for Schizophrenia and Antipsychotic Treatment: a Systematic Review

Abstract: Evidence from clinical, preclinical, and post-mortem studies supports the inflammatory/immune hypothesis of schizophrenia pathogenesis. Less evident is the link between the inflammatory background and two well-recognized functional and structural findings of schizophrenia pathophysiology: the dopamine-glutamate aberrant interaction and the alteration of dendritic spines architecture, both believed to be the “quantal” elements of cortical-subcortical dysfunctional network. In this systematic review, we tried to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 323 publications
1
39
0
Order By: Relevance
“…The extent to which antipsychotics modulate receptor activity is essential to ensure proper processes of neurite outgrowth, synaptogenesis, and spine organization [ 65 ]. In this framework, antipsychotics have shown a different capability to regulate PSD composition and spine architecture by exhibiting different pharmacodynamic profiles and acting through epigenetic mechanisms [ 65 , 66 , 67 , 68 , 69 ]. Specifically, aripiprazole and clozapine were found to increase PSD-95 protein levels, the number of dendritic spines, and the number of PSD puncta in cortical neuron cultures [ 70 ].…”
Section: The Postsynaptic Density: a Molecular Hub Involved In Neuron...mentioning
confidence: 99%
“…The extent to which antipsychotics modulate receptor activity is essential to ensure proper processes of neurite outgrowth, synaptogenesis, and spine organization [ 65 ]. In this framework, antipsychotics have shown a different capability to regulate PSD composition and spine architecture by exhibiting different pharmacodynamic profiles and acting through epigenetic mechanisms [ 65 , 66 , 67 , 68 , 69 ]. Specifically, aripiprazole and clozapine were found to increase PSD-95 protein levels, the number of dendritic spines, and the number of PSD puncta in cortical neuron cultures [ 70 ].…”
Section: The Postsynaptic Density: a Molecular Hub Involved In Neuron...mentioning
confidence: 99%
“…Preclinical studies in mice showed that maternal immune activation affects dopamine receptor expression, increasing dopamine levels in the striatum and decreasing D2R levels in adult offspring [ 434 , 435 ]. Alterations in cytokine homeostasis may correlate with the pathogenesis of schizophrenia, probably with a link to alterations in dopaminergic and glutamatergic signaling [ 435 ]. IL-1β appears to result in abnormal glutamate release and subsequent neurotransmitter accumulation that induces neuronal death [ 436 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fernandez-Egea et al showed that patients affected by schizophrenia have increased numbers of natural killer cells, naïve B cells, memory T cells, and monocytes and decreased numbers of dendritic cells, regulatory T cells, and CD4 + T cells in the blood [ 470 ]. Typical antipsychotics decrease the plasma levels of IL-6 and IL-6 receptor (IL-6R) [ 471 ], while atypical antipsychotics, such as clozapine and risperidone, increase the concentrations of IL-2R, IL-6, and TNF-α [ 435 , 472 , 473 ]. Clozapine has been demonstrated to interfere with multiple steps of the inflammatory response [ 474 ] and inhibit microglial activation [ 475 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from and beyond their action at dopaminergic and other central receptors, antipsychotic treatment has been demonstrated to modify brain expenditure energy metabolism and impact mitochondria function [ 24 , 25 , 26 ]. The relevance of regulating mitochondrial functions lies in the possible modulation of antioxidant intracellular pathways and other mechanisms involved in cell viability and survivance [ 26 , 27 , 28 ]. The potential modulation of mitochondria function and oxidative stress by antipsychotics is in line with a role for oxidative stress in schizophrenia and related psychosis [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%